METHOD AND SYSTEM TO DERIVE GLYCEMIC PATTERNS FROM CLUSTERING OF GLUCOSE DATA - SCHAIBLE Thomas (2017)
Described are methods and systems for determining clusters of glucose data that can be utilized to provide insights to the person with diabetes, such as, for example, when a certain number of measurements during a predetermined time period is less than a predetermined threshold so that the subject is notified that the number of glucose measurements is less than optimum for management of diabetes.